PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS FLIPBOOK PADA MATERI MAKHLUK HIDUP DALAM EKOSISTEM DI KELAS V SDN SATAK 2 - LINTANG, GITA PRAMESTI ADDIANA WAHYU; ZUNAIDAH, FARIDA NURLAILA; NURMILAWATI , MUMUN (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
This research aims to 1) Find out the validity of flipbook-based interactive media on living creatures in ecosystems in class V at SDN Satak 2. 2) Find out the practicality of flipbook-based interactive media on living things in ecosystems in class V at SDN Satak 2. 3) Find out the effectiveness interactive media, flipbook-based material about living things in ecosystems in class V at SDN Satak 2. This research uses the ADDIE development model with the research subjects being class V students at SDN Satak 2. This research uses the ADDIE development model with the research subjects being class V students at SDN Satak 2. The research uses the ADDIE development model with the research subjects being fifth grade students at Satak Elementary School. 2. The research goes through five stages in accordance with the ADDIE development which consists of analysis, design, development, implementation and evaluation. The data collection instruments used were observation, interviews, pre-test and needs analysis questionnaires, material and media validation questionnaires, teacher and student questionnaires, pre-test and post-test questions. The results of this research are 1) The results of media validation meet the validity criteria with a score percentage of 86%, and the results of material validation with a score percentage of 84.42%. 2) The results of media practicality can be seen from the results of the limited scale test with a score percentage of 85.71% and the results of the wide scale test with a score percentage of 91.42%, for the user response questionnaire the teacher obtained a score percentage of 92%. 3) The results of media effectiveness can be seen from the results of the pre-test and post-test on a limited scale, obtaining a score percentage of 84%, for a wide scale, obtaining a score percentage of 82%. ABSTRAKPenelitian ini bertujuan untuk 1) Mengetahui kevalidan media interaktif berbasis flipbook pada materi makhluk hidup dalam ekosistem dikelas V SDN Satak 2. 2) Mengetahui kepraktisan media interaktif berbasis flipbook pada materi makhluk hidup dalam ekosistem dikelas V SDN Satak 2. 3) Mengetahui keefektifan media interaktif berbasis flipbook pada materi makhluk hidup dalam ekosistem dikelas V SDN Satak 2. Penelitian ini menggunakan model pengembangan ADDIE dengan subjek penelitian siswa kelas V SDN Satak 2. Penelitian ini melalui lima tahap sesuai dengan pengembangan ADDIE yang terdiri dari análisis, desain, pengembangan, implementasi, dan evaluasi. Instrumen pengumpulan data yang digunakan adalah observasi, wawancara, pre-tes dan angket analisis kebutuhan, angket validasi materi dan media, angket guru dan siswa, soal pre-test dan post-test. Hasil dari penelitian ini adalah 1) Hasil validasi media memenuhi kriteria kevalidan dengan presentase skor 86%, dan hasil validasi materi dengan presentase skor 84,42%. 2) Hasil kepraktisan media dapat dilihat dari hasil uji skala terbatas dengan presentase skor 85,71% dan hasil skala luas dengan presentase skor 91,42%, untuk angket respon pengguna guru mendapatkan presentase skor 92%. 3) Hasil keefektifan media dapat dilihat dari hasil pre-test dan post-test skala terbatas mendapatkan presentase skor 84%, untuk skala luas mendapat presentase skor 82%.